2007
DOI: 10.1159/000109625
|View full text |Cite
|
Sign up to set email alerts
|

A radiation hybrid map of river buffalo <i>(Bubalus bubalis)</i> chromosome 1 (BBU1)

Abstract: The largest chromosome in the river buffalo karyotype, BBU1, is a submetacentric chromosome with reported homology between BBU1q and bovine chromosome 1 and between BBU1p and BTA27. We present the first radiation hybrid map of this chromosome containing 69 cattle derived markers including 48 coding genes, 17 microsatellites and four ESTs distributed in two linkage groups spanning a total length of 1330.1 cR5000. The RH map was constructed based on analysis of a recently developed river buffalo-hamst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…A set of linked markers on the telomeric region of BBU1q showed a rearrangement when compared to the sequence from bovine chromosome 1, revealing an inversion in the region flanked by the markers rs29021684 and COPB2 (Figure 1). In the previous RH maps constructed for this buffalo chromosome (Miziara et al, 2007;Amaral et al, 2008), an inversion in the same region was also observed when compared to the bovine chromosome 1.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A set of linked markers on the telomeric region of BBU1q showed a rearrangement when compared to the sequence from bovine chromosome 1, revealing an inversion in the region flanked by the markers rs29021684 and COPB2 (Figure 1). In the previous RH maps constructed for this buffalo chromosome (Miziara et al, 2007;Amaral et al, 2008), an inversion in the same region was also observed when compared to the bovine chromosome 1.…”
Section: Discussionmentioning
confidence: 61%
“…Its genome is organized in five pairs of bi-armed chromosomes, 19 pairs of acrocentric chromosomes, and a pair of X and Y sex chromosomes. The largest chromosome in the river buffalo karyotype, BBU1, is a sub-metacentric chromosome with reported homology between BBU1q and bovine chromosome 1 and between BBU1p and bovine chromosome 27 (Iannuzzi et al, 2003;Miziara et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenet Genome Res 2009;124:106-111 107 linkage maps are lacking for river buffalo and few RHmaps to single chromosomes are available for this species (Amaral et al, 2007;Strafuzza et al, 2007;Miziara et al, 2007;Iannella et al, 2008). In sheep, a linkage map is available (Maddox et al, 2001) but only a few RH-maps have been determined so far (Tetens et al, 2007;Wu et al, 2007;Drögemüller et al, 2008).…”
Section: Fish-mapping Comparison Between Bbu7 and Oar6mentioning
confidence: 99%
“…For this study, we carried out the steps from preparing input files and computing two‐point LOD scores through to solving a restricted travelling salesman problem that assigns a cR position to each frame and placed marker in a unified instance. To compute linkage groups, we used a pairwise LOD score threshold of 7.0, which is greater than the thresholds used in previous river buffalo chromosome maps (Miziara et al. 2007; Stafuzza et al.…”
Section: Cattle‐derived Markers From Btax Mapped With the Bburh5000 mentioning
confidence: 99%